Endothelial lesion and complement activation in patients with Scleroderma Renal Crisis - Pérez,Ney Arencibia (2019)
Abstract In kidney biopsies reviews, scleroderma renal crisis (SRC) is characterized by vascular endothelial injuries, C4d deposits on peritubular vessels, and acute and chronic injuries coexisting on the same biopsy. The clinical signs of thrombotic microangiopathy (TMA) are described in systemic sclerosis (SSc), nevertheless, it has not been related to acute injuries described on kidney biopsies. We report a case of SRC in a patient with scleroderma-dermatomyositis overlap syndrome, which also showed clinical and histopathological data of TMA. On fundus examination, a severe acute hypertensive retinopathy was found. The kidney biopsy showed severe endothelial damage with widening of mucoid cells at the level of the intima, focal concentric proliferation on most small arterioles, and C3, C4d, and IgM deposits along the capillary walls. The genetic study of complement only showed the presence of membrane cofactor protein (MCP) risk haplotypes, without other genetic complement disorders. We understand that in a patient with TMA and SSc, the kidney damage would be fundamentally endothelial and of an acute type; moreover, we would observe clear evidence of complement activation. Once further studies correlate clinical-analytical data with anatomopathological studies, it is likely that we will be forced to redefine the SRC concept, focusing on the relationship between acute endothelial damage and complement activation.